The Legend of Korra : turf wars - Konietzko, Bryan; DiMartino, Michael Dante; Koh, Irene (Comic book artist); Ng, Killian; Piekos, Nate (Milwaukie, OR : Dark Horse Books, 2017)
"Relishing their newfound feelings for each other, Korra and Asami leave the Spirit World, but find nothing in Republic City but political hijinks and human vs. spirit conflict. A pompous developer plans to turn the new spirit portal into an amusement park, potentially severing an already tumultuous connection with the spirits. What's more, the triads have realigned and are in a brutal all-out brawl at the city's borders--where hundreds of evacuees have relocated! In order to get through it all, Korra and Asami vow to look out for each other--but first, they've got to get better at being a team and a couple!"--Provided by publisher.
Description based on volume 1.
Part one: colors by Vivian Ng ; lettering by Nate Piekos of Blambot ; cover by Heather Campbell with Jane Bak.
Keywords: Spirits -- Comic books, strips, etc; Real estate developers -- Comic books, strips, etc; Evacuation of civilians -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Comic books, strips, etc; Comics (Graphic works); Fantasy comics; Comics (Graphic works); Graphic novels; Science fiction comics; Fantasy comics; Fiction; Graphic novels; Science fiction comics